The maturity of strategic networks' governance: Proposal of an analysis model - Marione Winkler; Douglas Wegner; Clea Beatriz Macagnan (Administrative Sciences, 2023)
Strategic Networks (SNs) consist of dozens to hundreds of organizations that work together to achieve common goals but remain legally independent. Because most SNs are managed by hired professionals rather than member companies, more structured governance models are recommended as the number of members grows. In addition, removing the network members from management roles allows for the emergence of a conflict of interest and the problem of information asymmetry. The purpose of this study is to propose a model for assessing the maturity level of SNs' governance. Using Design Science Research (DSR), a model of 34 items was developed to measure the maturity level of SN governance and serve as a guide for analyzing this type of inter-organizational collaboration. Using these indicators can provide opportunities for governance system improvements, resulting in better management of SNs.
Keywords: 350; cooperation; design science research; SN governance; strategic SNs